Positive effects of dietary approach for the treatment of hypertension - Maja Vuković; Biljana Mijović; Miloš Maksimović; Vesna Lazić (Биомедицинска истраживања, 2022)
According to the World Health Organization (WHO) and the Interna tional Society for Hypertension, elevated blood pressure is defined as the blood pressure the readings of which consistently range ? 140 mmHg systolic and/or 90 mmHg diastolic. Having in mind the fact that hypertension is one of the leading risk factors for cardiovasluar disease, kidney failure and premature mortality, it is clear that preventive mea sures should be imposed before the diagnosis is established. The main nutritional measures used in preventing hypertension are: weight loss, Dietary Approaches to Stop Hypertension (DASH diet), reducing salt and alcohol intake and increasing potassium intake. The aim of this paper was to show the preventive effect of the DASH diet on hypertension onset in normotensive patients as well as to highlight that the diet is an integral part of hypertension treatment, in addition to the use of drug therapy for hypertensive patients .
Keywords: diet; DASH diet; hypertension